The Effectiveness of Kahoot-Based Information Service in Improving Students' Critical Thinking Skills - Khoiriyah, Isnaul; Yuliana, Anis Tri; Astutik, Choli (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2026)
This study aims to analyze the effectiveness of information services utilizing Kahoot media in improving the critical thinking skills of tenth-grade students at MA Nurul Amien Pagarbatu. The method used was a quantitative approach with a One Group Pretest–Posttest design. All 10 students were selected as research subjects using a saturated sampling technique. Data were collected using a test instrument and then analyzed using descriptive statistics, normality tests, paired sample t-tests, and N-gain calculations. The research findings showed an increase in students' average scores. The paired sample t-test results obtained a significant value, indicating a significant difference between before and after the treatment. Furthermore, the N-gain value fell into the moderate category. Based on these results, it can be concluded that Kahoot-based information services have proven effective in improving students' critical thinking skills.